2016
DOI: 10.1016/j.ejvs.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Normal Exercise Oximetry in the Calf in Patients with Peripheral Artery Disease and Limiting Calf Claudication

Abstract: Ex-tcpO2 is negative in more than 20% of tests performed in patients with an ABI under 0.90 and a history of calf claudication. In most cases, when excluding re-tests and non-limiting or non-calf claudication on the treadmill, non-calf ischemia or a non-vascular limitation occurring during the test were observed. This observation supports both the value of treadmill testing in patients with calf claudication assumed to be of arterial origin (ABI<0.90) and the use of Ex-tcpO2 to detect non-calf ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Indeed we previously showed that up to 20% of patients with claudication and an abnormal ABI can have normal oximetry results as a consequence of nonvascular limitation. 21 Thus, the highly selected remaining population had apparent unilateral PAD (based on ABI value), strictly unilateral symptoms ( via history and treadmill evaluation and on the similar side), and confirmed exercise-induced ischemia on the symptomatic side (based on exercise oximetry). In these patients, we estimated the intensity of ischemia on the asymptomatic limb using the lowest DROPmin value of each limb (buttock or calf) and calculated the proportion of tests still revealing a significant exercise-induced ischemia (DROPmin < −15 mmHg) on the asymptomatic (both by history and on treadmill) and unaffected (normal ABI) limb.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed we previously showed that up to 20% of patients with claudication and an abnormal ABI can have normal oximetry results as a consequence of nonvascular limitation. 21 Thus, the highly selected remaining population had apparent unilateral PAD (based on ABI value), strictly unilateral symptoms ( via history and treadmill evaluation and on the similar side), and confirmed exercise-induced ischemia on the symptomatic side (based on exercise oximetry). In these patients, we estimated the intensity of ischemia on the asymptomatic limb using the lowest DROPmin value of each limb (buttock or calf) and calculated the proportion of tests still revealing a significant exercise-induced ischemia (DROPmin < −15 mmHg) on the asymptomatic (both by history and on treadmill) and unaffected (normal ABI) limb.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ABI at rest is frequently normal if lesions are not located on the measured axis (such as lesions of the internal iliac artery) [ 16 ]. Furthermore, we recently showed that 14.8 to 20.0% of patients with an abnormal ABI at rest have no exercise induced ischemia while exercise-induced ischemia can be found in 35.4% of patients with a normal ABI at rest [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-oximetry can be used to detect exercise-induced ischemia for patients referred for claudication of unknown, debatable, or arterial-suspected origin [ 15 , 19 ]. Its specific interest is to detect isolated proximal ischemia (as can result from internal iliac artery lesions), or exercise-induced hypoxemia as a cause or worsening factor of walking impairment [ 15 , 18 , 19 ]. Exercise-oximetry has been used as a routine in the last 20 years in our service for patients complaining walking limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Aetiological diagnosis of claudication of the lower limb is important. We have used transcutaneous oxygen pressure (TcpO2) at exercise in the last 20 years, to argue for the vascular origin of exercise‐related pain during treadmill tests (Abraham et al, 2018; Gernigon et al, 2013; Henni et al, 2018; Jaquinandi et al, 2007; Signolet et al, 2016). As a routine, we use a constant load (3.2 km/hr, 10% slope) standard procedure.…”
Section: Introductionmentioning
confidence: 99%